Strengthening resilience: decentralized decision-making and multi-criteria analysis in the energy-water-food nexus systems - Haji, Maryam; Namany, Sarah; Al-Ansari, Tareq (Frontiers in Sustainability, 2024)
The Energy-Water-Food (EWF) nexus is a complex and multidimensional system, in which the energy, water and food resources are strongly interconnected. EWF nexus systems are seriously threatened by natural hazards (e.g., climate change and extreme weather events) along with other human-driven threats, including rapid population growth, urbanisation, terrorism, and geopolitical uncertainty. As such, integrated analysis, as encouraged by the EWF nexus can facilitate the identification of essential connections and potential conflicts that may arise in the planning and operation of resource systems. Moreover, in order to consider immediate shocks and long-term pressures, it is imperative to prioritize the strengthening of EWF system resilience by incorporating robust and efficient resource management strategies, which consider various dimensions of sustainability and security such as technical, environmental, economic, and societal aspects. Decentralisation is one concept that has the potential of improving the resilience of nexus systems faced to the multiple risks governing them through reducing single points of failure and enabling swifter responses to sudden shocks and continuous volatilities. However, in order to achieve a holistic system resilience through decentralisation, the assessment of the different risks impacting each nexus sector is fundamental, yet it can be particularly challenging. Therefore, the objective of this study is to review the currently available resilience assessment methods for the EWF nexus system. The systematic literature review will connect various assessment methods used within decentralisation studies that are applied to improve the resilience performance of the EWF nexus system. A total of 84 journal papers were evaluated. The review demonstrates that the deployment of multi-criteria decision-making framework based on composite indicators can be effective in addressing risks and uncertainties within EWF systems. Furthermore, findings of this review illustrate complementary connections between decentralisation and resilience concepts, which when integrated with the EWF nexus approach, can be effectively utilised for integrated sustainable resource management.